PENGARUH REAL EARNING MANAGEMENT TERHADAP ARUS KAS OPERASI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Felicianus Adi Nugroho; Dewi Ratnaningsih (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
This study aims to determine the efect of real earnings management which is a proxy of earnings management to the predictive ability of fnancial reports through the company’s operating cash fow. Researchers also consider the infuence exerted by the quality of audits of the relationship between real earnings management with the company’s operating cash fow. Samples are manufacturing companies listed in Indonesia Stock Exchange during the period of observation 2010-2012.Berdasarkan criteria previously set contained 249 corporate data used in this study. The results of this study revealed that real earnings management has an infuence on the predictive ability of fnancial statements through operating cash fow. Quality audits can also afect earnings management actions undertaken by the company and consequently also of the operating cash fow of the company. Overall audit quality may afect the actions of earnings management and certainly also the predictive ability of corporate fnancial statements.Keywords: real earnings management, operating cash fow, and audit quality.